Structure of the maturing 90S pre-ribosome in association with the RNA exosome - Lau, Benjamin; Cheng, Jingdong; Flemming, Dirk; La Venuta, Giuseppe; Berninghausen, Otto; Beckmann, Roland; Hurt, Ed (Molecular cell, 2021)
Ribosome assembly is catalyzed by numerous trans-acting factors and coupled with irreversible pre-rRNA processing, driving the pathway toward mature ribosomal subunits. One decisive step early in this progression is removal of the 5' external transcribed spacer (5'-ETS), an RNA extension at the 18S rRNA that is integrated into the huge 90S pre-ribosome structure. Upon endo-nucleolytic cleavage at an internal site, A(1), the 5'-ETS is separated from the 18S rRNA and degraded. Here we present biochemical and cryo-electron microscopy analyses that depict the RNA exosome, a major 3'-5' exoribonuclease complex, in a super-complex with the 90S pre-ribosome. The exosome is docked to the 90S through its co-factor Mtr4 helicase, a processive RNA duplex-dismantling helicase, which strategically positions the exosome at the base of 5'-ETS helices H9-H9', which are dislodged in our 90S-exosome structures. These findings suggest a direct role of the exosome in structural remodeling of the 90S pre-ribosome to drive eukaryotic ribosome synthesis.